The Use of Movie to Enhance Undergraduate Students’ Listening Comprehension Ability - Muhamad Alpha Aulia; Adityo, Adityo (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2022)
This study aims to determine the extent to which movie might enhance students' listening ability. The participants in this study were seventh-semester undergraduates from the Department of English Language Education at The University of Muhammadiyah Malang. Five of the class A students were selected to participate in the study. This study used a pre-experimental design for its investigation. Participants in the study were instructed to watch four Sherlock movie from the third season and then write a synopsis of each episode. Further, the synopsis data would be evaluated by software called P LEX to determine the extent to which the movie improves the listener's vocabulary. The result of the test indicates that watching movie significantly improves students' vocabulary acquisition. Among all research participants, vocabulary levels 1, 6, and 7 indicated the least improvement, ranging from 9 to 25.6 percent, while vocabulary level 3 demonstrated the greatest improvement, ranging from 99.1 to 143.5 percent. Furthermore, it can be seen from the data set that students comprehended the vocabularies effectively as they recalled the movie scenes and make an infer on what the scene’s context is about.